Vitalisation of Multicultural Education through the Integration of the Epistemology of the Meaning of Ta’aruf Q.S. al-Hujurāt: 13 - Khalfiah, Yuliani; Anwar, Khairil; Mahfuzh, Taufik Warman (Aphorisme: Journal of Arabic Language, Literature, and Education, 2025)
This study aims to vitalise epistemology by exploring alternative philosophical foundations from QS. Al-Hujurāt: 13 and operationalising them through synthesis with critical and multicultural education theories. This study employs a qualitative research Design with a library research approach to examine the epistemology of ta‘āruf as articulated in QS Al-Hujurāt 13 and its relevance to the revitalisation of multicultural education. Data collection is conducted through documentation techniques by systematically identifying, classifying, and reviewing relevant texts and written sources. The data analysis employs a hermeneutic method to interpret the Qur’anic text contextually and dialogically, combined with qualitative content analysis to examine conceptual patterns and theoretical intersections between Islamic epistemology and multicultural education theories. The results reveal that the concept of “i ta'ārufū” (getting to know each other) in the verse encompasses Ta’aruf Epistemology, a relational, dialogical, and socially transformative knowledge paradigm. Vitalisation is achieved by synthesising and integrating Freire’s concept of dialogue-praxis with Banks’ five dimensions of multicultural education, resulting in a transformation model at the levels of curriculum (oriented towards experience), pedagogy (teacher as learner and facilitator), and evaluation (authentic assessment).